Pengaruh Kualitas Produk, Kualitas Pelayanan dan Persepsi Harga Terhadap Kepuasaan Pelanggan Larut Coffe - Indra Heri Rukmana (CV. ULIL ALBAB CORP, 2023)
The purpose of this study was to determine the effect of product quality, service quality and price perception partially and simultaneously on customer satisfaction at Larut Coffe. This research uses quantitative methods. The population in this study were the customers of Larut Coffe. The sample used in this study was 100 respondents who were customers of Larut Coffe. In this study, purposive sampling was used, namely a technique with certain criteria, which in this study were buyers who came to Larut Coffe two or more times. The data collection method used is by distributing questionnaires to consumers to get 100 respondents according to predetermined criteria. Then the researcher conducted a survey after first testing the validity and reliability. The data analysis method used in this study is regression analysis. The results of the study prove that partially product quality has a significant and significant effect on customer satisfaction, the service quality variable has a significant effect on customer satisfaction and the price perception variable has a significant effect on customer satisfaction at Larut Coffe.